Recent advancements in image‐enhanced endoscopy in the pancreatobiliary field - Haruka Toyonaga; Tsuyoshi Hayashi; Kazuki Hama; Ryo Ando; Tatsuya Ishii; Kenta Yoshida; Toshifumi Kin; Masayo Motoya; Kuniyuki Takahashi; Akio Katanuma (DEN Open)
Abstract Image‐enhanced endoscopy (IEE) has advanced gastrointestinal disease diagnosis and treatment. Traditional white‐light imaging has limitations in detecting all gastrointestinal diseases, prompting the development of IEE. In this review, we explore the utility of IEE, including texture and color enhancement imaging and red dichromatic imaging, in pancreatobiliary (PB) diseases. IEE includes methods such as chromoendoscopy, optical‐digital, and digital methods. Chromoendoscopy, using dyes such as indigo carmine, aids in delineating lesions and structures, including pancreato‐/cholangio‐jejunal anastomoses. Optical‐digital methods such as narrow‐band imaging enhance mucosal details and vessel patterns, aiding in ampullary tumor evaluation and peroral cholangioscopy. Moreover, red dichromatic imaging with its specific color allocation, improves the visibility of thick blood vessels in deeper tissues and enhances bleeding points with different colors and see‐through effects, proving beneficial in managing bleeding complications post‐endoscopic sphincterotomy. Color enhancement imaging, a novel digital method, enhances tissue texture, brightness, and color, improving visualization of PB structures, such as PB orifices, anastomotic sites, ampullary tumors, and intraductal PB lesions. Advancements in IEE hold substantial potential in improving the accuracy of PB disease diagnosis and treatment. These innovative techniques offer advantages paving the way for enhanced clinical management of PB diseases. Further research is warranted to establish their standard clinical utility and explore new frontiers in PB disease management.